Documentation Technical Debt: A Qualitative Study in a Software Development Organization - Mendes, Leonardo; Cerdeiral, Cristina; Santos, Gleison (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2019: Anais do XXXIII Simpósio Brasileiro de Engenharia de Software, 2019)
Context: Technical debt refers to software development pending issues that may cause great damages in the future if not resolved in the present. The longer the payment is delayed, the greater the interests. Documentation technical debt comprises problems concerning non-existent, inadequate or incomplete software projects' documentation. Motivation: Despite the importance of documentation, there is a lack of reports on how documentation technical debt occurs in software development organizations. Objective: We executed a qualitative study in a software development team of a large public health organization aiming to identify causes that led to documentation technical debts, along with possible consequences of their occurrence, and best practices to avoid documentation problems. Method: We interviewed four members of the development team and codified the collected data using thematic analysis technique. Results: We identified 35 causes, 20 consequences, and 15 best practices. Conclusions: We identified several problems that led to poor documentation despite the existence of well-defined processes. Also, we could observe how organizational culture influences the processes execution, and how team members' technical expertise can minimize the effects of poor documentation.